PERANAN ETIKA PROFESI NOTARIS SEBAGAI UPAYA PENEGAKAN HUKUM - M. Khafit Prasetyo; M. Wlidan Jumanuba; Ayatulloh Masyhudi (JURNAL ILMIAH NUSANTARA, 2024)
The goal of the state is to create legal certainty for society. Notaries are public officials who are obliged to provide services to people who need their services. These services are interpreted in a broad sense, which does not only include legalizing personal documents, making authentic deeds, or providing legal advice related to notarial matters. The notary's code of ethics is all the moral rules determined by the Indonesian Notary Association which apply to all members of the association and other people who assume and carry out the position of Notary both in the performance of their office and in daily life. The notary's code of ethics includes the ethics of Notary services, the ethics of fellow Notaries, the ethics of carrying out the duties and positions of Notaries, as well as the duties and authority to enforce the code of ethics by supervisory institutions at Notaries. The notary's code of ethics contains material elements regarding obligations, prohibitions, exceptions and sanctions that will be imposed on a notary who is proven to have violated the code of ethics. The Notary Code of Ethics aims to ensure that the Notary profession can be carried out professionally with motivation and orientation towards intellectual skills as well as arguing rationally and critically and upholding moral values.